Conjoint Analysis of Consumer Preferences for The Marketing Promotion Mix for Foam Matters Products - Ika Rahayu Puspaningrum, (Proceeding of International Management Conference and Progressive Papers, 2023)
Promotion is an important element that can be used to introduce products or services to consumers. Choosing the right marketing promotion mix strategy will benefit the company. This study was conducted to determine consumer preferences for the marketing promotion mix (advertising, sales promotion and direct marketing) of BigFoam Foam Mattress products at PT Subaindo Cahaya Polintraco. This research uses a survey by distributing questionnaires to respondents. Respondents of this study are consumers who have bought and used foam mattresses from PT Subaindo Cahaya Polintraco. Purposive side was used as the data collection technique. The collected data is processed by conjoin analysis. There are three marketing promotion mixes used as variables or called attributes, and nine sub-attributes called levels. The results of the best combination chosen by respondents based on consumer preferences are a marketing promotion mix using TikTok social media advertising, sales promotion with fresh money bonuses, and direct marketing through salespeople.